Android Based Student Monitoring Information System - Agus Trison Septianto; Mohammad Suryawinata (Procedia of Engineering and Life Science, 2021)
Information systems play a very important role in the world of education to convey academic and non-academic information. At SMPN 2 Sedati, information is conveyed to parents about academic and non-academic achievements at the end of the semester. There is no information system that can provide development for students with mobile devices. The purpose of this research is to make a student monitoring information system to make it easier for teachers and bk in providing information on grades, presence, achievement, violations to parents of students efficiently and quickly. System testing is carried out by the blackbox method with 100% results without any errors, while user testing using the User Aceptance Testing method gets results for teachers and bk according to the material needed, for parents the application is very easy to use and the information obtained is very useful. It can be concluded that the application of the Android-Based Student Monitoring Information System is very useful and makes it easy for teachers and Bk to provide information to parents of students about the development of their children.